Developing a Fairtrade rice supply chain from Myanmar: achievements, challenges, lessons. (1st June 2021) - Williams, George
Abstract : Traidcraft Exchange and its sister business Traidcraft plc have been developing Fair Trade supply chains for over three decades. As core certified 'Fairtrade' products have become mainstream in UK markets since the late 1990s, Traidcraft Exchange has focused energies on bringing innovative supply chains and small-producer organisations into the wider Fair Trade system. The case study presented here is of rice sourced from smallholder farmers in Myanmar's Ayeyarwady region: the world's first Fairtrade product from Myanmar. The case study illustrates how Traidcraft Exchange's explicit focus on small producers and innovating new supply chains from 'left behind' communities can work in practice. It explains challenges faced at both the supplier and market end. It seeks to show how broader programmatic aims to strengthen small producer skills and organisational capacity to engage with trade on fairer terms can mitigate risks associated with export trade to the challenging UK market.